Implementing Accrual Accounting in the Public Sector - Flynn, Suzanne (Technical Notes and Manuals; Technical Notes and Manuals ;, 2016)
This technical note and manual (TNM) explains what accrual accounting means for the public sector and discusses current trends in moving from cash to accrual accounting. It outlines factors governments should consider in preparing for the move and sequencing of the transition. The note recognizes that governments considering accounting reforms will have different starting points across the public sector, different objectives, and varying coverage of the existing financial statements, it therefore recommends that governments consider each of these, and the materiality of stocks, flows and entities outside of government accounts when planning reforms and design the sequencing and stages involved accordingly. Building on international experiences, the note proposes four possible phases for progressively increasing the financial operations reported in the balance sheet and operating statement, with the ultimate aim of including all institutional units under the effective control of government in fiscal reports.